2007
DOI: 10.1124/dmd.106.014605
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 (Breast Cancer Resistance Protein/Mitoxantrone Resistance-Associated Protein) ATPase Assay: A Useful Tool to Detect Drug-Transporter Interactions

Abstract: ABSTRACT:The ATPase assay using membrane preparations from recombinant baculovirus-infected Spodoptera frugiperda ovarian (Sf9) cells is widely used to detect the interaction of compounds with different ATP-binding cassette transporters. However, Sf9 membrane preparations containing the wild-type ABCG2 transporter show an elevated baseline vanadate-sensitive ATPase activity, which cannot be further stimulated by substrates of ABCG2. Therefore, this assay system cannot be used for the detection of ABCG2 substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Of the drugs tested, Ko143 was the most effective inhibitor of ABCG2 function. It had previously been shown to inhibit ABCG2 at nanomolar concentrations by blocking ATPase activity of the transporter (35). We derived an ED 50 for maximal inhibition of ABCG2 at the BBB of 6.3 ± 1.8 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Of the drugs tested, Ko143 was the most effective inhibitor of ABCG2 function. It had previously been shown to inhibit ABCG2 at nanomolar concentrations by blocking ATPase activity of the transporter (35). We derived an ED 50 for maximal inhibition of ABCG2 at the BBB of 6.3 ± 1.8 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…To verify further the interaction of the analogs with ABCG2, an ATPase assay was used. This is another useful assay for studying the interaction of transport substrates with ABCG2, since ATP hydrolysis is coupled with the transport function of this transporter (Glavinas et al, 2007;Gallus et al, 2014). The analogs were found to stimulate ATP hydrolysis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that sulfasalazine activates ABCG2 ATPase 10) in membrane based assays. In this work the detailed kinetic characterization of sulfasalazine-ABCG2 interaction is described using direct vesicular transport and ATPase assays at pH 7.0 and pH 5.5.…”
mentioning
confidence: 99%